2010
DOI: 10.1177/000348941011900103
|View full text |Cite
|
Sign up to set email alerts
|

Level of Complete Dissection of the Ethmoid Sinuses with a Computed Tomographic Image Guidance System

Abstract: Even with the use of a CT image guidance system, a complete ethmoidectomy was still difficult to achieve. Residual ethmoid sinus cells were more commonly found along the lamina papyracea than along the skull base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Table shows the laterality of the residual ethmoid cells found on the lamina papyracea, skull base, and posterior to the horizontal portion of the preserved middle turbinate basal lamella. The greatest number of residual ethmoid cells were found on the lamina papyracea (similar to the Rawlings and Han cadaver study, discussed later in this paragraph), followed by the skull base, with the lowest number of residual ethmoid cells found near the basal lamella. Figures and illustrate the number of residual ethmoid cells found on the lamina papyracea and the skull base/basal lamella, respectively.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Table shows the laterality of the residual ethmoid cells found on the lamina papyracea, skull base, and posterior to the horizontal portion of the preserved middle turbinate basal lamella. The greatest number of residual ethmoid cells were found on the lamina papyracea (similar to the Rawlings and Han cadaver study, discussed later in this paragraph), followed by the skull base, with the lowest number of residual ethmoid cells found near the basal lamella. Figures and illustrate the number of residual ethmoid cells found on the lamina papyracea and the skull base/basal lamella, respectively.…”
Section: Discussionsupporting
confidence: 70%
“…Again, our current data also indicate a slightly larger overall number of residual ethmoid cells on the lamina compared to the skull base, but this difference was not significant ( p > 0.05). Interestingly, as a secondary outcome measure the Rawlings and Han study found that there was no difference in terms of residual cells between the left and right ethmoid sinuses ( p > 0.05). In contrast, Dessi et al reported on their series of 1192 endoscopic sinus surgery procedures performed on 386 patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, prevalence of residual ethmoid cells seen in revision FESS patients was reported to be 65% for anterior, and 75% for posterior ethmoid cells . Even with the use of computed tomography (CT) image guidance, a thorough ethmoidectomy is still difficult to achieve, with numbers of residual anterior ethmoid and posterior ethmoid air cells reported to be 1.4 and 1.2, respectively …”
mentioning
confidence: 99%
“…TAPE is beneficial in recurrent ESS, especially when familiar landmarks are missing. As it was shown that at times even navigation precludes a total ethmoidectomy, TAPE maybe a solution for those cases, especially with a lateral PE cell 13. Contrary to revision ESS, where appreciation of the constant landmarks may be challenging, the posterior antral wall is immediately noted.…”
Section: Discussionmentioning
confidence: 99%